PENINGKATKAN KETERAMPILAN MASYARAKAT DESA JERUK MANIS MELALUI PEMANFAATAN KULIT JERUK BALI MENJADI PRODUK MANISAN - Imam Rozy Zarkasih, Muhammad; Resmayanti, Resmayanti; Handayani, Ridhatul; Septiandani, Risna Septiandani; Saputra, Irfan; Aini, Kuratun; Fikrina, Garin; Anisa Putri, Baiq; Ramadan, Galih; Asyari, Adam; Muthahanas, Irwan (Jurnal Wicara, 2025)
Desa Jeruk Manis has great agrarian potential, especially in the Citrus maxima plantation sector. While its fruit pulp has high economic value, pomelo peels are often discarded as waste despite containing bioactive compounds such as flavonoids, antioxidants, and dietary fiber. Utilizing pomelo peels as the main ingredient for making candied products can provide economic and social benefits for the village community, particularly for micro, small, and medium enterprises (MSMEs). This program was implemented through training sessions for housewives and MSMEs in Desa Jeruk Manis, consisting of socialization and hands-on practice in making candied pomelo peels. The process involved several stages, including washing, soaking, boiling, and packaging. The results of this initiative showed that the training successfully enhanced the community’s skills in processing pomelo peels into high-value products. The resulting candied product demonstrated good sensory quality in terms of taste, texture, and shelf life, with significant potential to be developed as a village specialty product. Additionally, this program contributed to increasing household incomes and supported the circular economy concept by repurposing agricultural waste. Therefore, utilizing pomelo peels for candied production is expected to become a sustainable economic empowerment strategy in Desa Jeruk Manis and other areas with similar potential.